Factors affecting personal customers' trust in traditional banking: case of the Baltics. Issue 4 (4th July 2017) - Skvarciany, Viktorija; Jurevičienė, Daiva
Abstract: Nobody disputes that trust is an important issue in choosing a financial service provider, especially in the area of new forms of banking. The goal of this paper is to assess the most important determinants of trust in traditional banking. The study was conducted in the Baltics and personal customers had to rank the distinguished factors. Using correlation analysis and binary logistic regression model it was found that the most significant factor influencing trust in all countries is provided information by the bank. In addition, in Lithuania – bank's characteristics, in Latvia – customers' risk perception and bank's characteristics, in Estonia – respondents' experience of cooperation with a bank were highlighted as significant. The following measures of fit are used in order to describe the created logistic models: contingency table test, Nagelkerke pseudo-R 2, Pearson chisquare test, Wald test. However, there is a limitation – the survey was conducted online. Nevertheless, as Internet penetration rate is high enough in investigated countries (from 76 percent in Latvia to 91 percent in Estonia), survey results can be adapted for at least seventy-five percent of each country's population. The findings have implications on the development of the strategy and the policy of commercial banks.